The use of the Septuagint in Afrikaans Bible translations - Rooy, Herculaas F. van (HTS teologiese studies, 2020)
The Bible Society of South Africa is currently in the process of publishing a new Afrikaans translation of the Bible. In its introduction, the 1983 translation refers to earlier Hebrew manuscripts used but not to the early translations, such as the Septuagint or Vulgate. The 2020 translation uses the ancient versions but tries to remain as faithful as possible to the Biblia Hebraica Stuttgartensia. When comparing instances where the 2020 translation refers to the ancient versions, it becomes clear that the two earlier Afrikaans translations used them as well, 1983 more than 1933/53. The use of the Septuagint in these three translations is elucidated by a number of examples from the books of Ezekiel and 1 Samuel. All three Afrikaans translations of the Old Testament made use of the ancient versions in some instances where the Masoretic Text (MT) presented serious problems. This was done to a lesser extent in the 1933/53 translation. This translation does not discuss the issue in its introduction and contains no notes referring to the practice. The 1983 translation used the Septuagint and the other versions more than the earlier translations did, and has notes about its preferences in some, but not all, instances. The 2020 translation will contain notes in all instances where it deviates from the MT, and even in some instances where it translated the MT, but where the Septuagint or other ancient versions have important variant readings.Contribution: The 1933/53, 1983 and 2020 Afrikaans translations of the Bible used the Septuagint to solve some text-critical issues in the Masoretic Text. The 1983 translation indicates this with footnotes in some instances and the 2020 translation in all instances. Bible translation is related to the core focus of HTS.